Does trade, technology or education expel traditional sectors? Evidence from the collapse of South Korea’s silk sector - Rakotoarisoa, M.; Kim, S. (Wiley, 2008)
Rapid economic growth and development often drives out traditional activities. We determine how increased trade, technology, and access to education in South Korea led to the collapse of its silk sector. Results show that although the imports of silk yarn and fabric reduced domestic silk output and prices, trade liberalization was not the sole contributor to the collapse. Inelastic labor demand for unskilled workers, skill-biased technology, and especially increased access to education all led to a sharp rise in the relative wage of unskilled workers, and the ensuing rise in production costs contributed to the silk sector's collapse.